Optimization of harvesting and post-harvest drying methods of Ocimum africanum Lour. for production of quality essential oil. Issue 6 (2nd November 2018) - Padalia, Rajendra C.; Singh, Ved R.; Bhatt, Gunjan; Chauhan, Amit; Upadhyay, R.K.; Verma, Ram S.; Chanotiya, Chandan S.
ABSTRACT: The influences of cropping seasons, crop maturity stages and wilting period on essential oil composition of Ocimum africanum Lour. var. CIM-Jyoti, grown at foothills agroclimatic conditions of northern India, were studied and compared using gas chromatography–flame ionization detector and gas chromatography–mass spectrometry. Altogether, 28 constituents, forming 91.8–99.1% of the total oil composition, were identified by comparing their retention indices and mass spectral data. The essential oil content was found to vary from 0.38% to 0.66% during different maturity stages with maximal in full bloom stage. Citral (55.0–75.5%), ( E )-γ-bisabolene (2.6–9.5%), nerol (1.7–8.9%), geraniol (1.5–6.5%), linalool (1.1–6.0%), β-caryophyllene (0.7–3.2%), α-humulene (0.4–2.7%) and 6-methyl-5-hepten-2-one (≤0.03–2.1%) were identified as the characteristic constituents of the essential oil of O. africanum . Significant variations in the essential oil content and qualitative chemical composition were noticed in different harvesting stages of two cropping seasons.